Repeated computed tomography scanning reveals morphological development of burrows produced by the tiger pistol shrimp Alpheus bellulus. - Miyu Umehara; Koji Seike; Seishiro Furuyama (PLoS ONE)
The burrow morphology of endobenthic organisms reflects their subsurface ecology. In this study, we observed the three-dimensional development of burrows produced by the tiger pistol shrimp Alpheus bellulus in a tank using an X-ray computed tomography (CT) scanner. CT scanning was performed at 10-30 min intervals immediately after the start of burrow construction. The three-dimensional morphology (surface area, volume, depth, length, and diameter) of burrows at each observation time was imaged and measured. In addition, the rate of increase of each parameter was calculated. Surface area, volume, length, and depth rapidly increased immediately after the start of the experiment in all burrows. Subsequently, there was a reduction in the rate of increase at 40 min after the start of excavation for burrow depth, at 75 min for length, and at 90 min for surface area and volume. Although there were large differences in burrow diameter among the burrows immediately after the start of the experiment, all burrows reached nearly identical diameters after 90 min. Changes in burrow morphology were not observed in most of the burrows more than 210 min after the start of the experiment, meaning that A. bellulus can create burrows that are sufficient for survival within this time period. The use of CT scans in this study clarified the developmental process of the three-dimensional structure of A. bellulus burrows and is applicable to various burrow-producing organisms. Our results provide new insights into the development of burrow structures.